The Variety and Meaning of The Community Tradition of Coastal Bungo Wedung Indonesia - Mahfudlah Fajrie (Universitas Airlangga, 2020)
Bungo Village, Subdistrict of Wedung Indonesia, is one of the regions that still upholds the traditions of the region as a form of preserving culture. Along with the development of technology and science, there are many traditions in the village that are considered not modernist by the people. Therefore, some village government and community heads in the village of Bungo, Wedung District, are trying to maintain traditions in their area as a form of preserving local traditions or culture and when developed can have potential for regional income. Coastal traditions in the Bungo Village area that are still carried out include Apitan, Syawalan, and Alms of Earth, the meaning of this tradition as a form of community gratitude to God. There is a Nyadran tradition, the Panji Kusuma Cultural Kirab is a tradition carried out as a form of respect for coastal communities and in memory of the services of heroes who have established villages in the coastal region. There is also the tradition of Keong Keli, Barian, Kembang Sayang, which basically implies a form of community effort to avoid doom and danger. This research was conducted using ethnographic methods, data collection using in-depth interviews and observation. From the coastal traditions carried out by the Bungo people, it is shown that coastal communities depend on the sea for their livelihoods and the wealth of natural resources to survive.